2021
DOI: 10.1111/jade.12365
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Online Learning Practice in the Interior Design Studio

Abstract: The COVID-19 pandemic has led most countries to adopt precautionary isolation measures to prevent the spread of the virus. In this context, teaching through online studios has become a necessity. This study aimed to identify students' practical experiences in fully online interior design studios and determine whether these experiences differ according to students' educational levels to help improve and ensure the quality of online design education. The participants were 69 female interior design students. A qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Because to obtain the desired benefit from online education environments, appropriate pedagogical approaches should be employed (Schlosser & Simonson 2006). In a similar study, Alawad (2021) found that novice students who do not have design experience in a traditional face‐to‐face studio had more positive views about online design teaching methods. Despite this, it has been suggested that different teaching strategies for online design education should be investigated (Alawad 2021).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Because to obtain the desired benefit from online education environments, appropriate pedagogical approaches should be employed (Schlosser & Simonson 2006). In a similar study, Alawad (2021) found that novice students who do not have design experience in a traditional face‐to‐face studio had more positive views about online design teaching methods. Despite this, it has been suggested that different teaching strategies for online design education should be investigated (Alawad 2021).…”
Section: Introductionmentioning
confidence: 92%
“…In a similar study, Alawad (2021) found that novice students who do not have design experience in a traditional face‐to‐face studio had more positive views about online design teaching methods. Despite this, it has been suggested that different teaching strategies for online design education should be investigated (Alawad 2021). Emphasising the importance of the integration of teaching strategies in both studies reveals the necessity of conducting the online design teaching process in line with a teaching strategy.…”
Section: Introductionmentioning
confidence: 92%
“…Alawad (2021) discovered that newer students were more satisfied with online design studios than were those close to graduating. Students with lower grade point averages (GPAs) experienced more difficulties in the online context than those with higher GPAs (Figlio et al, 2010; Xu & Jaggars, 2013), and students exposed to technology adapt faster to online learning (Liu et al, 2007; Stewart et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Design educators who teach design studio courses have been reluctant to offer online education (Alawad, 2021;Bender, 2005;Bender & Good, 2003;George, 2017) and viewed the online or blended learning environment as inadequate believing it cannot replace face-to-face studio activities (Fleischmann, 2016;Mohammed, 2017;Saghafi et al, 2012;Salama & Wilkinson, 2007;Ubell, 2016). It was often perceived that online design studios would not be successful (Silva & Lima, 2008) and could decrease the quality and effectiveness of the learning experience (Ubell, 2016).…”
Section: Online Design Studiomentioning
confidence: 99%
“…This transition also lays the foundation in terms of understanding the interior design process; a step by step comprehension of the development from the getting the brief, to concept development, materializing, budgeting, leading to the finalization and realization stage. The development of this skill is significant not only for the upper years of interior design higher education, but also to develop a systematic approach for graduates' professional lives (Abercrombie, 1990;Afacan, 2016;Alawad, 2021;Konkel, 2014). This enables a deeper approach to interior design, creating more meaningful spaces that enhance the life quality of users.…”
Section: Introductionmentioning
confidence: 99%